Implementation of Disaster and Risk Management Policy in the East-Cost of Madagascar - Faramalala Rakotondrasoa (Magister Ilmu Administrasi Publik, 2016)
The implementation of Disaster and Risk Management (DRM) policy in Madagascar was a great success and an evolution from its birth until today thanks to these different stakeholders. This implementation that has helped a lot the improvement of living standards of the local population in eastern of Madagascar before, during and after the passage of an aleas. Yet blocking factors even been known because the implementation is not fully satisfactory. This study aims to analyze the problems of implementation. Despite unceasing improvement, the local population still has a very low impact strength and after each cyclone crossing ,the same situation returns. To improve this implementation, I will also suggest few solutions that could solve these problems, so that each level actors can improve their own policy and work method. Note that these solutions were made after long lived with the community.